Estrategias digitales en el Spa de Uñas Cleopatra del cantón Babahoyo, durante el período 2024. - Medina Bajaña, Veycky Elizabeth (2024)
This case study entitled “Digital strategies at Cleopatra Nail Spa in Babahoyo canton, during the period 2024.” focused on the analysis of the digital strategies used by Cleopatra Nail Spa, located in Babahoyo canton. Despite being a business with several years in the market, it faces difficulties in positioning itself and attracting new clients due to the lack of a comprehensive digital approach. Challenges such as inconsistency in publications and inefficient use of social networks are identified, which limits its visibility and growth in a highly competitive and digitalized environment. Through interviews and a SWOT analysis, the need to optimize the spa's digital strategies to improve its online presence and customer loyalty is evident. In effect, it is concluded that, with these improvements, Cleopatra Nail Spa will be able to strengthen its position in the local market, attract more clients and guarantee its sustainability over time, adapting to the trends and demands of the modern consumer. The Spa has used social media such as Instagram and Facebook to promote its services, but lack of optimization has limited its reach, especially among the younger audience. Poor planning and lack of knowledge in network management have affected the effectiveness of its digital strategies. The SWOT analysis reveals strengths such as loyalty through personalized promotions, but also weaknesses in the inconsistency of content and low interaction, as well as threats such as competition.